From teleconnection to telecoupling: taking stock of an emerging framework in land system science. Issue 2 (3rd March 2016) - Friis, Cecilie; Nielsen, Jonas Østergaard; Otero, Iago; Haberl, Helmut; Niewöhner, Jörg; Hostert, Patrick
Abstract : Land use change is influenced by a complexity of drivers that transcend spatial, institutional and temporal scales. The analytical framework of telecoupling has recently been proposed in land system science to address this complexity, particularly the increasing importance of distal connections, flows and feedbacks characterising change in land systems. This framework holds important potential for advancing the analysis of land system change. In this article, we review the state of the art of the telecoupling framework in the land system science literature. The article traces the development of the framework from teleconnection to telecoupling and presents two approaches to telecoupling analysis currently proposed in the literature. Subsequently, we discuss a number of analytical challenges related to categorisation of systems, system boundaries, hierarchy and scale. Finally, we propose approaches to address these challenges by looking beyond land system science to theoretical perspectives from economic geography, social metabolism studies, political ecology and cultural anthropology.